Certain Geometric Properties of the Canonical Weierstrass Product of an Entire Function Associated with Conic Domains. (20th September 2022) - Selvakumaran, K. A.; Rajaguru, P.; Purohit, S. D.; Suthar, D. L.
Abstract : In this paper, we determine the radius of λ -uniform convexity, λ -starlikeness, and α -convexity of order δ for the Weierstrass canonical product of an entire function as a root having smallest modulus and argument ϕ of a functional equation. As special cases, we also determine the radius of λ -uniform convexity, λ -starlikeness, and α -convexity of order δ for the entire function 1 / Γ .